pengembangan video pembelajaran pemeliharaan sasis dan pemindah tenaga kendaraan ringan - endra duwi_riadi (JURNAL VOKASI DEWANTARA (JVD), 2023)
The aims of this research are (1) to develop learning video media to complete the PSPTKR subject module for class XI of Industrial Vocational High School Yogyakarta. (2) determine the feasibility of the PSPTKR subject practical learning video. This research is a research and development (Research and Development) with a 4D model. The subjects in this study were material experts, media experts and students of class XI TKR SMK Perindustrian Yogyakarta as users of the learning video media that was developed. The object of research is teaching materials. The collection technique uses a questionnaire/questionnaire, the instrument used is a measuring tool such as a questionnaire, observation guidelines and interview guidelines used by researchers to collect data in research, data analysis techniques using quantitative descriptive. The results of the research show that (1) the development of learning video products to complete the PSPTKR subject module can be done using the development of the four-D model consisting of the define, design, develop, disseminate, and (2) the development of learning videos that are suitable for use as teaching materials. , this is evidenced by the results of the percentage of material expert validation, which is 75.75% in the "very feasible" category. Meanwhile, media experts received a score of 98.1% in the "very decent" category. The last stage is product testing. The product trial was carried out in two stages, namely a trial with a small group with a number of respondents 10 students obtained a percentage of 75.95% in the "very feasible" category, and a large group trial with a number of respondents 22 students getting a score of 78.69% , with the category “very decent”.